(untitled) (Revista Tempo e Argumento, 2022)
In 1912, Karl Lingner created the German Hygiene Museum Dresden profiting from the Dresden International Hygiene Exhibition 1911. Lingner aimed to build a permanent building for the museum, but due to the Great War and post-war economic crisis in Germany, the permanent building was not opened until 1930. In the Weimar Republic, the museum circulated internationally through traveling exhibitions and the sale and donation of collections and exhibits. This circulation comprised a global exchange promoting health education that included Latin America. In keeping with German foreign cultural policy of the period, the German Hygiene Museum played an active role in the transatlantic cultural relations and the German-Latin American exchange, functioning as "a cultural propaganda institute". In this article, we explore the transnational circulation of objects and collections between Dresden and Latin America which was also associated with international efforts to promote public health. Keywords: Public Health; Health Education; Cultural Propaganda; German-Latin American Relations; Transnational and Global History.